2022
DOI: 10.3390/vetsci9020049
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Natural SARS-CoV-2 Infection in Domestic Rabbits

Abstract: We tested 144 pet rabbits sampled in France between November 2020 and June 2021 for antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by microsphere immunoassay. We reported the first evidence of a natural SARS-CoV-2 infection in rabbits with a low observed seroprevalence between 0.7% and 1.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Protein sequences and structural modeling analysis revealed that ACE2 is widely distributed in animal species, representing a potential risk of cross-species transmission for this virus ( 6 , 7 ). SARS-CoV-2 infection has been reported in companion animals including cats, dogs, rabbits, ferrets and minks ( 8 , 9 ). Animal experimental infections indicate that cats can infect SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Protein sequences and structural modeling analysis revealed that ACE2 is widely distributed in animal species, representing a potential risk of cross-species transmission for this virus ( 6 , 7 ). SARS-CoV-2 infection has been reported in companion animals including cats, dogs, rabbits, ferrets and minks ( 8 , 9 ). Animal experimental infections indicate that cats can infect SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The hepatitis E virus has been recently identified in rabbits [19]. In France, a recent study reported evidence of natural SARS-CoV-2 infection in rabbits that was attributed to direct contact with human patients [20]. A recent study carried out in experimental conditions highlighted the evidence of viral shedding in infected rabbits, despite the low seroprevalence and the lack of clinical signs [21].…”
Section: Introductionmentioning
confidence: 99%
“…The use of young, immunocompetent, and healthy New Zealand White rabbits in this study, however, may not reflect virus shedding and disease in other rabbit breeds or rabbits at different ages [ 38 ]. A recent study reported the first evidence of natural SARS-CoV-2 infections among domestic rabbits in France, most likely acquired from a COVID-19-positive owner [ 39 ]. However, it is likely that rabbits are quite poorly susceptible to the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%